‘Side‐hustling’ in commercial agriculture among young university graduates in Ghana - Thomas Yeboah; James Boafo (Geo: Geography and Environment)
Abstract Youth unemployment and under‐employment in Ghana represent a major concern for policymakers and young people themselves. While the agriculture sector has been touted as having the potential to offer employment to the teaming youth, there is little research focusing on the steps and pathways with which young university graduates navigate to engage in commercial cashew production to build their livelihood. Drawing on qualitative research conducted with young university graduates in Nkoranza, a community in the Bono East Region of Ghana, we explore the steps and pathways with which they navigate engagement in commercial cashew production for the export market. A key finding of the study is that young university graduates engage in cashew production as a ‘side‐hustle’ to supplement their income from their primary occupations, with some important gender and generational dimensions. We also found that young university graduates rely on social relations and existing land market to access the needed resources including land, credit and labour to engage in cashew production. The findings also indicate that young university graduates view cashew farms as long‐term investments and have no plans to return to the city in future. Based on these findings, we argue that youth employment is not about a single job and that social relations continue to be a key resource in youth livelihood building. We further argue that despite the popular and existing policy narratives that young people are not interested in agriculture and/or rural areas, and that migration from rural to urban areas is the de facto option, investment and engagement in commercial agriculture as a side‐hustle in addition to family concerns, rising cost of living in the cities and children's education motivate young university graduates to remain in the rural economy.